Postdated pregnancy: a risk factor for adverse maternal and perinatal outcome - Gupta, Shweta; Kumari, Ruby; Vijaya; Bharti, Aastha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The study’s objective is to contrast maternal and perinatal outcomes in postdated and term pregnancies in order to better understand the related risks and difficulties. Methods: A retrospective observational study was conducted at the Department of Obstetrics and Gynaecology, ANMMCH, Gaya, between June 2019 and May 2023. The study comprised 474 women, separated into two groups: term (37-40 weeks) and postdated (>40 weeks). Data were gathered from medical records, with an emphasis on maternal and fetal problems. The statistical analysis used Student’s t-tests and Chi-square. Results: The present study involving 474 pregnant women (postdated-186, term-288) revealed that postdated pregnancies had greater risks of maternal problems, such as postpartum hemorrhage (34 vs. 18 instances, p=0.0001), cervical tears (6 vs. 5 cases, p=0.354), as well as postpartum infections (8vs.11 case, p=0.8137). Furthermore, perineal injuries occurred more frequently in postdated pregnancies (15 vs. 7 incidence, p=0.0064). Fetal problems were also more common, with shoulder dystocia (4 vs. 5 case, p = 0.7426) and meconium aspiration (20 vs. 16 instances, p = 0.0497). The rate of fetal hypoxia was considerably higher in postdated pregnancies (8 vs. 6 instance, p=0.1756). A higher proportion of term pregnancies had no issues (250 vs. 128 instances, p=0.00001), indicating that term births are relatively safe. Conclusions: The study found that postdated pregnancies are associated with greater maternal and fetal problems, demanding close monitoring and timely interventions.